Le problème de la valence et de l’ordre des prédicats dans la conception des structures prédicat-arguments de Stanisław Karolak - Śmigielska, Beata (Neophilologica, 2013)
The predicate-arguments structure constitutes the frame of semantic grammar which was the subject of many years of study of Stanisław Karolak, an outstanding Polish linguist. The conception at hand here, based on analytic philosophy, focuses on the relations that occur among logic, language and the outside world. This, then totally new, approach to the description of language supplies us with necessary tools to conduct the analysis of conceptual relations nets, which reflect the situations taking place in the real world. At the deep level of language the predicates open one or more positions for different types of arguments, thus forming the predicate-arguments structure (proposition) invoking a given extra linguistic situation. One of the most difficult tasks of semantic grammar is to objectively show implications of different number and different types of arguments. The author studies valency and rank of chosen predicates, simultaneously giving thought to the method of their classification based within the frames of the approach adopted in the article.